Predicting Radiative Heat Transfer in Oxy-Methane Flame Simulations: An Examination of Its Sensitivities to Chemistry and Radiative Property Models - Hassan Abdul-Sater; Gautham Krishnamoorthy; Mario Ditaranto (Journal of Combustion)
Measurements from confined, laminar oxy-methane flames at different O2/CO2 dilution ratios in the oxidizer are first reported with measurements from methane-air flames included for comparison. Simulations of these flames employing appropriate chemistry and radiative property modeling options were performed to garner insights into the experimental trends and assess prediction sensitivities to the choice of modeling options. The chemistry was modeled employing a mixture-fraction based approach, Eddy dissipation concept (EDC), and refined global finite rate (FR) models. Radiative properties were estimated employing four weighted-sum-of-gray-gases (WSGG) models formulated from different spectroscopic/model databases. The mixture fraction and EDC models correctly predicted the trends in flame length and OH concentration variations, and the O2, CO2, and temperature measurements outside the flames. The refined FR chemistry model predictions of CO2 and O2 deviated from their measured values in the flame with 50% O2 in the oxidizer. Flame radiant power estimates varied by less than 10% between the mixture fraction and EDC models but more than 60% between the different WSGG models. The largest variations were attributed to the postcombustion gases in the temperature range 500 K–800 K in the upper sections of the furnace which also contributed significantly to the overall radiative transfer.